PENGARUH 7-hydroxy-2-(4-hydroxy-3-methoxy-phenyl)- chroman-4-one BIJI Swieteniamacrophylla King TERHADAP GLUKOSA DAN High Density Lipoprotein DARAH Rattusnorvegicus YANG DIINDUKSI STREPTOZOTOCIN DAN NICOTINAMIDE - , DIMAS NUGROHO KURNIAWAN; , Dra. Prasetyastuti, Apt, M. Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Degenerative diseases has been an emerging issues around the world. Diabetes mellitus is one of the disease that became attention. Approximately 347 million people in the world has diabetes, in Indonesia diabetes mellitus prevalenceâs increased too. Besides hyperglycemia, in DM patients often shown abnormality on lipid metabolism, known as dyslipidemia. World Health Organization recommend to research an alternative medicine related with diabetes mellitus, one of them is seed of S. macrophylla King. Flavonoid of S. macrophyllaâs seed (7-hydroxy-2-(4-hydroxy-3-methoxy-phenyl) chroman-4-one) has been reported to have an anti inflamation effect, anti mutagenic effect, anti tumor and effective to treat diabetic rat. Objective: This study was conducted to determine the effect of 7-hydroxy-2-(4-hydroxy-3-methoxy-phenyl) chroman-4-one S. macrophylla King seed on blood level glucose and HDL in the rat induced by strepzotocin and nicotinamide. Methods: This research is quassi-experimental with the utilization of pre-test and post-test control design. Thirty six male laboratory mice (Rattus norvegicus) used as subjects. They were divided into six groups